The influence of muscles activation on the dynamical behaviour of the tympano-ossicular system of the middle ear - Gentil, F (2014)
The human ear is a complex biomechanical system and is divided into three parts: outer, middle and inner ear. The middle ear is formed by ossicles (malleus, incus and stapes), ligaments, muscles and tendons, which transfers sound vibrations from the eardrum to the inner ear, linking with mastoid and Eustachian tube. In this work, a finite element modelling of the tympano-ossicular system of the middle ear was developed. A dynamic study based on a structural response to harmonic vibrations, for a sound pressure level (SPL) of 110, 120 and 130 dB SPL applied in the eardrum, is presented. The connection between the ossicles is made using a contact formulation. The model includes the different ligaments considering its hyperelastic behaviour. The activation of the muscles is based on the constitutive model proposed by previous work. The harmonic responses of displacement and pressure obtained on the stapes footplate, for a frequency range between 100 Hz and 10 kHz, are obtained simulating the muscle activation. The results are compared considering the passive and active states. The results are discussed and they are in accordance with audiological data published with reference to the effects of the middle ear muscles contraction.